Establishing the link between poverty and changes in climatic conditions in the Philippines - Agustin L. Arcenas (University of the Philippines, School of Economics (UPSE), 2018)
This paper investigates whether changes in climatic conditions significantly contribute to incidence of poverty in the Philippines. Due to the lack of sufficient regional estimates of poverty, this study utilized food cpi data to proxy for poverty level. The relationship between poverty level and food cpi were tested and found to be moving in parallel direction, and hence, could be substituted for each other for this study's purposes. The relationship between poverty and food prices has also been verified in the literature, as higher food prices is the dominant variable that results in higher poverty levels. The results show that higher agricultural wages as well as extreme climate-influenced shocks such as El Ni\~no and La Ni\~na were significant determinants of poverty. Higher agricultural wage benefits agricultural workers, but the income effect may be small, and that overall, the net effect of is higher food prices that, in turn, exacerbates overall poverty. The negative impact of El Ni\~no and La Ni\~na on food prices (and therefore, poverty level) could be attributed to the consistent and appropriate government response to these weather shocks, which have stabilized supply of food. Government programs to stock up on rice during weather shocks, and the automatic assistance to farmers during calamities, have had the overall effect of neutralizing the potential poverty impacts of climate-related shocks. These are useful insights in carving out a climate-resilient economic development plan, and emphasize the importance of timely and appropriate government action and adaptation programs.
Keywords: Q11; Q15; Q18; Q20; Q21; Q54; 330; Poverty; El Ni\~no; La Ni\~na; climate change; food inflation